On the Existence of a Cyclic Near-Resolvable (6n+4)-Cycle System of 2K12n+9 - Raja'i Aldiabat; Haslinda Ibrahim; Sharmila Karim (Journal of Mathematics)
In this article, we prove the existence of a simple cyclic near-resolvable v-1/2-cycle system of 2Kv for v≡9  mod  12 by the method of constructing its starter. Then, some new properties and results related to this construction are formulated.